Effects of retrograde autologous priming on blood transfusion and clinical outcomes in adults: a meta-analysis. (May 2013) - Sun, P; Ji, B; Sun, Y; Zhu, X; Liu, J; Long, C; Zheng, Z
Objective: Reducing the priming volume is an effective means of decreasing hemodilution and blood transfusion during cardiopulmonary bypass (CPB). The patient's own blood was used to replace the crystalloid in the CPB circuit by retrograde autologous priming (RAP) in order to decrease the priming volume. Therefore, we performed a meta-analysis to investigate whether RAP could reduce blood transfusion and improve clinical outcomes. Materials and Methods: A comprehensive search was conducted for randomized, controlled trials (RCTs) exploring RAP in PubMed, Embase, The Cochrane Library, Google Scholar and Chinese literature databases (WanFang, WeiPu and CNKI). Clinical parameters and outcomes were focused on the lowest hematocrit (Hct) during CPB, the number of patients transfused blood intraoperatively, the number of patients transfused blood perioperatively, the number of blood units transfused, 24-hour chest tube drainage, hours to extubation, length of ICU stay, and length of hospital stay. Results: Ten trials, with a total of 1123 patients, were included. The number of patients transfused blood intraoperatively (RR = 0.39, 95% CI = [0.29, 0.53], p<0.00001, I 2 = 40%) and perioperatively (RR = 0.53, 95% CI = [0.43, 0.66], p<0.00001, I 2 = 0%) and the number of blood units transfused (SMD = -0.53, 95% CI = [-0.73, -0.33], p<0.00001, I 2 = 14%) were all significantly reduced in the RAP group. No differences in the hours to extubation (SMD = -0.11, 95% CI = [-0.33, 0.12], p=0.37, I 2 = 0%) and the length of ICU stay (SMD = -0.17, 95% CI = [-0.41, 0.08], p=0.18, I 2 = 0%) were observed between the two groups. Conclusion: Compared to conventional priming, RAP could reduce transfusion in adults significantly, but had no effect on clinical outcomes, comparing to conventional priming. Further studies involving RAP are expected to investigate if this technique is beneficial to the patient.